An evaluation of beta-hydroxybutyrate in milk and blood for prediction of subclinical ketosis in dairy cows. - Samiei, A.; Juan, Boo Liang; Ghorbani, G. R.; Hirooka, H.; Yaakub, Halimatun; Tabatabaei, Meisam (http://www.uwm.edu.pl/pjvsci/main.html, 2010)
The first objective of this study was to investigate the relationship between concentrations of beta-hydroxybutyrate (BHBA) in milk and blood to assess the reliability of the BHBA concentrations in milk measured by a semi quantitative keto-test paper to detect subclinical ketosis (SCK) in 50 fresh high-producing Iranian Holstein cows in Golestan Province, Iran. The second objective was the effects of SCK on milk yield and components. Concentrations of nonesterified fatty acids (NEFA) and BHBA were analyzed quantitatively in blood plasma and commercial keto-test paper was used for semi quantitative determination of BHBA concentration in milk. Milk yield was measured until 60 d after calving but milk compositions were measured until 30 d after calving. The mean plasma BHBA, milk BHBA, plasma NEFA, milk yield, milk fat percentage and milk fat: protein ratio were 1,234 micromol/L, 145 micromol/L, 0.482 mEq/L, 29.5 kg, 3.9% and 1.4, respectively. Fifty eight percent of the cows had SCK during the first month of lactation. High correlation coefficients were observed between blood BHBA and blood NEFA, and between blood and milk BHBA. The milk yield of cattle with SCK decreased (P < 0.01) but the fat percentage and milk fat: protein ratio increased (P < 0.01). The commercial keto-test paper used had a low false positive result at a cut-off point of 200 fmol of BHBA/L of milk. The results showed that the best time to assess SCK using the commercial keto-test paper was d 10, 14 and 17 after calving.